2002
DOI: 10.1192/bjp.181.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Dropping out of care: inappropriate terminations of contact with community-based psychiatric services

Abstract: In a CPS targeted to patients with severe mental illnesses, those who drop out of care are younger patients without psychoses who are generally satisfied with their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
66
2
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 31 publications
13
66
2
14
Order By: Relevance
“…Socioeconomic status and marital status had no significant effect on levels of early engagement. Whereas some studies have previously suggested that divorce, living conditions and socioeconomic status are significant predictors of disengagement (Baekeland and Lundwall, 1975;Bender and Pilling, 1985), our results are consistent with studies which show no association (Edlund et al, 2002;Rossi et al, 2002;Wang, 2007). The SOLES has good predictive value for eventual disengagement but further research is required to assess engagement scores in these groups at serial time points.…”
Section: Discussionsupporting
confidence: 88%
“…Socioeconomic status and marital status had no significant effect on levels of early engagement. Whereas some studies have previously suggested that divorce, living conditions and socioeconomic status are significant predictors of disengagement (Baekeland and Lundwall, 1975;Bender and Pilling, 1985), our results are consistent with studies which show no association (Edlund et al, 2002;Rossi et al, 2002;Wang, 2007). The SOLES has good predictive value for eventual disengagement but further research is required to assess engagement scores in these groups at serial time points.…”
Section: Discussionsupporting
confidence: 88%
“…17,18 Logistic regression analysis showed that those who were either moderately or very satisfied with their outpatient care were less likely to default. However, the specific aspects of outpatient care defaulters found unsatisfactory were not explored and this is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos [35][36][37] registraram taxas de abandono significantemente mais elevadas entre pacientes solteiros, enquanto que o contrário foi registrado por outros autores 38,39 . Pacientes mais jovens tiveram maiores taxas de abandono nos estudos de Young et al 38 , Edlund et al 40 e Rossi et al 37 . Melo & Guimarães 41 encontraram taxas de abandono signifi cantemente mais elevadas em pacientes que não recebiam passes de ônibus para a consulta com especialistas.…”
Section: Avaliação Do Abandono Ou Continuidade De Tratamentounclassified